Pengaruh Kompetensi SDM Terhadap kompensasi dan Kinerja Karyawan (Studi Pada Perusahaan Jasa Konstruksi Bersertifikasi ISO-9000 Di Provinsi Sulut) - Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS, 2014)
ISO 9000 certified construction service companies in North Sulawesi need to develop work performance related competence model that can be used as a standard to develop human resources. In the more competitive business environment, a company is demanded to empower and optimize all proprietary resource, including human resources. Dealing with human resources with different characters, attitudes, and ability and to make them able to work cooperatively is indeed a challenge. Human resources who have knowledge and expertise are needed in an organization, and this will in return require organizational commitment. (Ulrich, 1998). An employeeâs competence is valued based on his/her expertise and manifested in the form of salary. This of course relies on the individualâs capabilityÂ (person based pay) and nonÂ characteristic work (job based pay) Long (1998). The aims of this research are: 1). to analyze and explain theÂ significant influence of human resource variable on compensation. 2). to analyze and explain the significant influence of human resource competence variable on employeeâs performance.3). to analyze and explain the significant influence ofÂ compensation variable on employeeâs performance. This research samplesÂ 211 field employees. The data is sampled using propotional random sampling. Questioner is the main instrument to collect data, as well as to obtain secondary data of the related company. SEM (Structural Equation Model) is used to calculate and test research result data. Research result shows that: 1). Significant and positive influence between human resource competence toward compensation is strongly seen. 2). Significant and positive between human resource competence and employeeâs performance is strongly seen. 3). Significant and positive influence between compensation toward employeeâs performance. Key word: human resource competence, compensation , employeeâs performance.